DAMPAK REGULASI PEMBIAYAAN KESEHATAN TERHADAP EFEKTIFITAS RENCANA ANGGARAN RUMAH SAKIT STUDI KASUS DI RSI SITI HAJAR SIDOARJO - Raden Rizki Ansanta; Basuki Rachmat (Universitas PGRI Adi Buana, 2025)
The implementation of the BPJS Health financing system through the INA-CBGs (Indonesian Case Base Groups) scheme has posed significant challenges to the operational sustainability of hospitals, particularly Type B hospitals that predominantly serve BPJS patients. This study aims to analyze the impact of financing regulations on the effectiveness of hospital budget planning and management using a case study at RSI Siti Hajar Sidoarjo. The findings reveal that healthcare financing regulations significantly influence budget planning structures, service tariff adjustments, and the strategic role of hospital managerial elements in maintaining operational efficiency. Active involvement of owners, supervisors, and medical personnel in budget planning and evaluation processes is a key factor in achieving an effective and sustainable hospital budget. This study also addresses an empirical gap regarding the impact of INA-CBGs policies on budget effectiveness in faith-based Type B hospitals and a theoretical gap in integrating budgeting theory with New Institutional Theory within healthcare settings.